THE ASSESSMENT CRITERIA - Mamaziyayev, Zohid (Журнал иностранных языков и лингвистики, 2023)
Teachers and testers need to know the criteria used in assessing speaking. In this respect, they should be familiar with what is called ‘rating scales’ for assessing speaking though there is some apprehension regarding their effectiveness (North, 1996 and Brindely, 1998 cited in Luoma, 2004). Though it is difficult to discuss them in detail, some basic information should be mentioned as they are essential for those who do not have any idea about them like Uzbek student-teachers and even teachers. The following speaking scales are reviewed: